EMPRESAS BRASILEIRAS SOCIALMENTE RESPONSÁVEIS: UMA ANÁLISE DO IMPACTO DA ADERÊNCIA AO ISE SOBRE A RENTABILIDADE SOBRE O PREÇO DAS AÇÕES - GONÇALVES, ELISÂNGELA MASSELLI (2018)
The objective of this research is to investigate possible differences in terms of profitability and price of the shares between the participating and non-participating companies of the ISE (Corporate Sustainability Index) on BM & FBovespa, currently B3. The sample analyzed, chosen for convenience, is composed of ten companies from the Energy, Food, Telephone, Wood / Paint and Pulp and Paper sectors, two companies from each sector, one ISE participant and one non-participant. Comparative analyzes were carried out to show differences and similarities in terms of appreciation / devaluation of the company's market price through the financial indicators EBITDA / ASSETS, EBITDA / Net Revenue and ROI for the period from 2013 to 2017. The data (BM & FBovespa) (B3) and financial indicators ,were calculated based on the financial statements of the companies for the period under review. The Mann-Whitney statistical method was used for the mean test, and the results obtained showed that there were no statistically significant differences between the two groups of companies (socially responsible and market) in relation to the aspects analyzed, it was found that the financial performance of ISE companies in general behaves in the same way as non-participating companies, it was found that there are no financial advantages in participating in ISE, there are no influences on financial performance and no differences were found compared to comparative business finances. It does not have attractive advantages for organizations. We can also say that the clients of the analyzed companies are not concerned with the environmental sustainability of the companies, when they buy products or services, if they had, they would prefer the companies that are in the ISE, that would make them more profitable and the results of the tests carried out would be different